A Systems Approach for Evaluating the Effectiveness of Radiological and Nuclear Detection Architectures in Urban Areas. Issue 2 (20th August 2013) - Chatterjee, Samrat; Salazar, Daniel E.; Maya, Isaac
ABSTRACT A key mission for the Domestic Nuclear Detection Office (DNDO) is to build state and local capabilities through radiological and nuclear (RN) detection, support equipment, and training systems. To support DNDO's capabilities at local jurisdictional levels within the US interior, this study contributes to the state‐of‐the‐art by extending the systems engineering approach toward identifying challenges to the practical effectiveness of RN detection architectures protecting potential urban area RN target and source sites. The study outcomes point to the technological challenges that need to be addressed for a viable urban detection system. Characteristics of RN target and source sites are discussed, and a detection probability model for a system of detectors is presented. Different detection layouts are evaluated, and implementation impacts are estimated in terms of vehicular delays. The methodology is illustrated in a case study application for regions within the State of California.